The Development of WODA’S (Word of Our Daily) Book on Improving Students Vocabulary Mastery - Ilvi Ainun Nisa; Muh Shofiyuddin (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2023)
The purpose of this study was to develop a learning media that can be used to improve vocabulary acquisition in middle school students. The medium developed was his WODA book, which describes media developments in vocabulary instruction for middle school students. This study was conducted in an Islamic secondary school in Jepara with research and development as the research design. This learning media also includes interactive games and colorful pictures to teach vocabulary to middle school students. The research design was research and development using the ADDIE model, which consists of 's analysis, design, development, implementation, and evaluation. The researchers have completed this study to the implementation stage. Data was collected through verification results by learning media experts. In the media expert's results, the score rate in the effective category, and the lecture material expert reported that his was effective. According to the result analysis, WODA game book, with its highly interactive images and color display, can be effectively used as vocabulary learning media and has the potential to attract students to the learning process in middle school, but there is still a need It includes several points that I think are important. In particular, we will improve the content and variety of the game. Based on the results of the analysis, we found that it is possible to use Woda's playbook for teaching and learning English.